Original Articles: Translational Oncology - Longitudinal Brain Changes Associated with Prophylactic Cranial Irradiation in Lung Cancer. Issue 4 (April 2016) - Simó, Marta; Vaquero, Lucía; Ripollés, Pablo; Gurtubay‐Antolin, Ane; Jové, Josep; Navarro, Arturo; Cardenal, Felipe; Bruna, Jordi; Rodríguez‐Fornells, Antoni
ABSTRACT : Introduction: : The toxic effects of prophylactic cranial irradiation (PCI) and platinum‐based chemotherapy on cognition in the lung cancer population have not yet been well established. In the present study we examined the longitudinal neuropsychological and brain structural changes observed in patients with lung cancer who were undergoing these treatments. Methods: : Twenty‐two patients with small cell lung cancer (SCLC) who underwent platinum‐based chemotherapy and PCI were compared with two control groups: an age‐ and education‐matched group of healthy controls (n = 21) and a group of patients with non‐SCLC (NSCLC, n = 13) who underwent platinum‐based chemotherapy. All groups were evaluated using a neuropsychological battery and multimodal structural magnetic resonance imaging: T1‐weighted and diffusion tensor imaging at baseline (before PCI for SCLC and chemotherapy for NSCLC) and at 3 months after treatment. T1 voxel‐based morphometry and tract‐based spatial statistics were used to analyze microstructural changes in gray matter (GM) and white matter (WM). The European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire—Core Questionnaire was also completed. Results: : Patients with SCLC exhibited cognitive deterioration in verbal fluency over time. Structural magnetic resonance imaging showed decreases in GM at 3 months in the right subcortical regions, bilateral insular cortex, and superior temporal gyrus in patients with SCLC compared with both control groups. Additionally, patients with SCLC showed decreases in GM over time in the aforementioned regions plus in the right parahippocampal gyrus and hippocampus, together with changes in the WM microstructure of the entire corpus callosum. These changes had a limited impact on responses to the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire—Core Questionnaire, however. Patients with NSCLC showed no cognitive or brain structural differences after chemotherapy. Conclusions: : This longitudinal study documents moderate neuropsychological deficits together with notable brain‐specific structural changes (in GM and WM) in patients with SCLC after chemotherapy and PCI, suggesting that chemotherapy and especially PCI are associated with the development of cognitive and structural brain toxic effects.